Improving Public Understanding of Drug and Cosmetic Safety Through Depinka-Ko Counseling in Sukatani Village: Peningkatan Pemahaman Masyarakat Tentang Keamanan Obat dan Kosmetik Melalui Penyuluhan Depinka-Ko di Desa Sukatani - Steffi Noviana, Maria; Rosary Marbun, Ovie; Hidyatus’sabilah, Hidyatus’sabilah; Halimatushadyah, Ernie; Octavia Purnomo, Frida; Humaedi, Aji (Universitas Haji Sumatera Utara, 2025)
Drug and cosmetic safety is an important aspect of public health, especially in rural areas. This program aims to improve the understanding of the Sukatani Village community, especially PKK members, about health product safety symbols through participatory-based counseling. This community service activity uses an educational method through counseling accompanied by measuring the results using a questionnaire. To determine the effectiveness of the counseling, a pre-test and post-test were conducted. The pre-test results showed that the average level of public understanding of this topic was 43.6%. After the counseling, there was an increase in the average public understanding to 75.2%. Thus, this method has proven effective in supporting efforts to improve the quality of public health.